SOSIALISASI KESADARAN PAJAK SEJAK DINI PADA PENDIDIKAN DASAR DI KECAMATAN JOGOROTO JOMBANG - Dwi Ermayanti Susilo (Universitas Bina Taruna Gorontalo, 2023)
Speaking Tax is a program used to build awareness of the important role of tax in the development sector. This activity aims to provide an introduction to taxes to early childhood because they are the nation's younger generation and they also have to know taxes well. This socialization was carried out due to a lack of introduction about tax awareness to students and basic knowledge in tax education. From this problem, the purpose of this service is to determine the level of tax awareness at an early age for students and to determine the level of knowledge in tax education for students.